Does Survey Medium Affect Responses? An Exploration of Electronic and Paper Surveying in British Columbia Schools - Walt, Nancy; Atwood, Kristin; Mann, Alex (The Journal of Technology, Learning and Assessment, 2008)
The purpose of this study was to determine whether or not survey medium (electronic versus paper format) has a significant effect on the results achieved. To compare survey media, responses from elementary students to British Columbia’s Satisfaction Survey were analyzed. Although this study was not experimental in design, the data set served as a rich source for which to investigate the research question. The methods included reliability, item mean, factor analysis, response rate and response completeness comparisons across survey media. From the analyses, the differences between electronic and paper media in this study appear to be minor, and do not seem to have a significant effect on overall results. In conclusion, the medium does not seem to overly affect response patterns and does not pose any threats to the validity or reliability of survey results.